Malawi : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper develops a framework to study the macroeconomic and distributional implications of alternative Farm Input Subsidy Program (FISP) reforms in Malawi. The FISP is one of the largest social expenditure items in Malawi, aimed at improving food security and reducing poverty. The FISP program targets poor rural households and provides them with a coupon for a predetermined amount of fertilizer at a heavily subsidized rate. The results of the study discussed in this paper show how policies that seek to improve the efficiency of expenditure can be consistent with higher and more equitable growth. It also focuses on the macroeconomic and distributional impacts of reducing the subsidy rate for the FISP.